Diary of a wimpy kid : hard luck - Kinney, Jeff. (New York : Amulet Books, 2013)
"Greg Heffley's on a losing streak. His best friend, Rowley Jefferson, has ditched him, and finding new friends in middle school is proving to be a tough task. To change his fortunes, Greg decides to take a leap of faith and turn his decisions over to chance. Will a roll of the dice turn things around, or is Greg's life destined to be just another hard-luck story?"--Provided by publisher.
Keywords: Friendship -- Juvenile fiction; Fortune -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Juvenile fiction; Friendship -- Fiction; Luck -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Diaries -- Fiction; Humorous stories; Young adult fiction; Graphic novels; Humorous fiction